En equilibrio no hay crisis: crítica a los supuestos neoclásicos (2012)
This paper constitutes a critic to the neoclassical theory heart, ideological support of the neoliberal arguments whose connection with the current state of art around the economy teaching world, under supposed to the capitalism harmonic operation risen to the science category: balance, invisible hands, efficiency in the production, natural forces as laws of the market, inertial tendencies to the full and fair occupation in the productive resources, maximum effectiveness in all the orders, etc. Leaves from the rejection to the economy conception like "shortage science", centering in the Political Economy discussion: the study of the social relationships of production, distribution, accumulation and consumption, among social classes with conflictive interests, apparent in all the human life aspects.